Allelopathic activity of Azadirachta indica A.Juss. on Handroanthus serratifolius (Vahl) S.Grose (Research, Society and Development, 2022)
Allelopathy involves the direct or indirect, stimulating or inhibiting action, promoted by substances called allelochemicals which, when released into the environment, can interfere positively or negatively in the development and germination of surrounding species. The objective of this work was to evaluate the allelopathic potential of Azadirachta indica A.Juss (Meliaceae) leaves on seed germination and seedling development of Handroanthus serratifolius (Vahl) S.Grose (Bignoniaceae). The experimental design used was completely randomized with four treatments and a control group (distilled water). Each treatment consisted of four replicates of 15 seeds each. The aqueous extract was prepared by grinding 250 g of fresh leaves in 1 L of distilled water, where further dilutions were made at concentrations of 25%, 50%, 75% and 100%. Germination rate, germination speed index (IVG), radicle length and stem length were analyzed. In addition to the pH and osmolarity of the extracts. And the phytochemical prospection to determine the main classes of secondary metabolites. Seed germinability was only affected by the extract at 100% concentration. It was also observed a reduction in the length of the stems and radicles of seedlings subjected to extracts at the highest concentrations. The observed effect may be due to the presence of alkaloids, flavonoids and phenolic compounds, since these compounds have proven action on the development of seedlings.